THE ROLE OF SME-S ON TOURISM MARKETING – THE CASE OF ALBANIA - Matja, Leida (European Scientific Journal, ESJ, 2012)
Tourism is a priority sector in Albania. With its 13 % contribution to GDP and 233000 employed directly or indirectly annually, or 23,9 per cent of the total Albania jobs, it has become one of the most priority sectors promoted strongly even by the Government. Tourism marketing is always perceived as multi-parties effort toward a final aim, increase the country revenues. The efforts of the marketing are done from the Central Government, local Government as well as all single industry actors where the main role belongs to Tourism SME-s. This study aims to evidence the main techniques used by Tourism actors in Albania. It will also give suggestion to improve marketing techniques in order to increase efficiency and minimize the costs of useless marketing strategies followed by the above mentioned actors with emphasis to Tourism SMEs. It also gives recommendations on how the SME-s can improve their marketing performance in the market.